RA V5 N1, Message from the Editor in Chief and Guest Editor (January - April 2015) - Castro Borges, Pedro (Revista ALCONPAT, 2015)
JOURNAL OF THE LATIN-AMERICAN ASSOCIATION OF QUALITY CONTROL, PATHOLOGY AND RECOVERY OF CONSTRUCTION.http://www.revistaalconpat.orgWith great satisfaction we present the first number of the fifth year of the ALCONPAT journal.The aim of the journal is to publish case studies within the scope of the Association, namely quality control, pathology and recovery of constructions, including basic and applied research, reviews and documentary research.This edition presents our third Special Number, this time dedicated to Sustainable Cements and Concrete.The V5N1 number begins with a research from Spain, in which García-Lodeiro et al investigated the strength development and reaction products of various hybrid cements based on several industrial byproducts and very low clinker of Portland cement. They conclude that the use of solid activators allows the production of binders of very low clinker contents (20%)The second paper from Mexico and Switzerland by L. Y. Gómez-Zamorano et al deals with the use of pozzolanic supplementary cementitious materials as partial substitutes to Portland cement and evaluated the mechanical properties, microstructures and hydration reactions. The SCM were blast furnace slag, fly ash, metakaolin and a geotermal silica. Some replacement materials show strong reactivity, which lead to enhancements of the mechanical properties of up to 200% relative to the pure Portland cement.In the third paper from England and Australia, S. A. Bernal et al evaluate the effects of modifying the amount of water in alkali activated slag binders, in terms of the kinetics of reaction and structural development. The results indicate that there is no systematic correlation between the water contents, the strength development and the rate of reaction, indicating that there is an optimal value that favors the dissolution of the slag and the precipitation of cementitious reaction products.The fourth paper, by F. Baeza Brotons et al from Spain, studied binary and ternary combinations of sweage sludge ash (SSA) with fly ash, marble dust and rice husk ash as partial substitutes of portland cement in concretes with very low water ratios, similar to that used to make cinder blocks. The use of SSA reduced the density and strength compared to the reference specimens; however, the combination with the other by products enhanced the properties of the binders.Another paper from O. Burciaga Díaz et al. From Mexico, show results correlations of compressive strength and microstructural evolution of geopolymeric pastes exposed to high temperatures. The results from X-ray diffraction and infrared spectroscopy suggested the reorganization of the gels in the reaction products and the water evaporation; both phenomena reduce the strength of the binders after exposure to high temperature.The last but not least paper from Brazil authored by C. Britez et al, take on the concept of sustainable construction that has been undertaken in various engineering projects worldwide. As many researchers do not consider concrete as a sustainably attractive construction material, this paper brings elements towards changing such perception, while presenting an application of a high strength concrete in structural elements in a building from Sao Paulo, focusing on sustainability aspects.We are confident that the papers in this special number will become a reference for those readers involved in cases and research related to properties, structure and durability of Sustainable Cements and Concrete. We are grateful to all authors of this special number for their endeavors towards the preparation of high quality papers in time.It is noteworthy that the commitment and efforts from authors, reviewers, and editorial board during these 5 years, have positioned the Alconpat journal within the Indexes of Conacyt (National Council of Science and Technology of Mexico), Latindex and Scielo. Moreover, this number sets a landmark as the beginning of publication in English language.The Editorial BoardPedro Castro Borges                   José Iván Escalante GarcÃaEditor in Chief                                Guest Editor